Association study of LMP-1 expression and promoter methylation status of tumor suppressor gene RASSF1A in nasopharyngeal carcinoma - Ageng Brahmadhi Susanna Hilda Hutajulu, Dewi Kartika Harijadi, Rina Susilowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Nasopharyngeal carcinoma (NPC) is a cancer originating fromnasopharyngeal epithelial tissue. Genetic susceptibility,exposure to carcinogens, and Epstein-Barr virus (EBV) infection are the main factors in NPC development. Latentmembrane protein 1 (LMP-1) is a product of EBV genome, which is able to interact with various intracellular signalingpathways that leads to expression of many proteins, e.g DNA methyltransferase. The increase expression of DNAmethyltransferase could induce hypermetylation of tumor suppressor genes (TSG). Ras-association domain family1A (RASSF1A) is one of TSG that frequently hypermethylated in NPC cases. The aim of this study is to determinethe association between LMP-1 expression and promoter methylation status of RASSF1A in NPC patients. Theresearch subjects were 36 NPC patients of the Dr. Sardjito Hospital, Yogyakarta, Indonesia. Latent membraneprotein 1was stained immunohistochemically using monoclonal antibody OT21C. Ras-association domain family 1Amethylation statuswas examined by methylation specific PCR (MSP) of DNA isolated fromnasopharyngeal brushing.Chi-square analysis was conducted to examine the association between LMP-1 expression and methylation status ofRASSF1A with 95%confidence interval. Latent membrane protein 1 was expressed in 44.4%subjects. The scoresof LMP-1 expression were ranged from 0-8 (average of 1.56±2.16). Ras-association domain family 1A methylatedin 66.7% of subjects. Statistical analysis showed that there was a relationship between LMP-1 expression andmethylation status of RASSF1A (p<0.05). Statistical analysis also showed association between LMP-1 expressionscore and RASSF1A methylation status (p<0.05). It can be concluded that there was an association between theexpression of LMP-1 and RASSF1A methylation status in NPC patients.Keywords: LMP1 - RASSF1A – NPC – hypermethylation - DNA methyltransferase - methylation specific PCR